Green Criminology and Environmental Harm: The Case for the (Potential) Crime of Ecocide under International Law (Dhaka University Law Journal, 2025)
Several decades have been spent by a significant number of international lawyers and environmental activists advocating for the establishment of a universally recognised legal definition of ecocide. This definition would refer to the widespread and long-lasting destruction of the environment attributable to human activities. They intend to establish ecocide as a criminal act under international law. On the other hand, ecocide has only recently gained momentous criminological interest over the last decade, coinciding with the emergence of green criminology, a critical criminological perspective that specifically addresses environmental crime and the detrimental effects of climate change. This article explores the role of green criminology in conceptualising ecocide as a legal notion or scheme to address the criminal acts or omissions that cause climate change and environmental degradation. It suggests that collaboration between international lawyers, environmental activists, and green criminologists is crucial to develop a comprehensive understanding of ecocide and push for its recognition as a crime within the framework of international law.Dhaka University Law Journal, 2024, 35 (1), 217-234